2011
DOI: 10.1093/jac/dkr438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotypic tropism prediction tests compared with in vitro co-receptor usage in HIV-1 primary isolates of diverse subtypes

Abstract: Comparing genotypic assays for HIV-1 co-receptor use with a cell-culture phenotypic assay could provide more reliable results of sensitivity and specificity for the detection of X4 strains than comparing them with recombinant assays, considered as gold standard. In general, except for subtype F isolates, there is a good correlation for tropism prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 44 publications
5
32
1
1
Order By: Relevance
“…Geno2pheno with a 10% cutoff has been recommended for V3 genotyping (22). Recent evaluations of genotypic algorithms for predicting tropism of non-B subtype viruses showed good agreement with the phenotype, but the CRF01-AE subtype was not included (6,23). Moreover, we have shown that these genotypic tools are not valid for predicting the tropism of subtype D viruses (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geno2pheno with a 10% cutoff has been recommended for V3 genotyping (22). Recent evaluations of genotypic algorithms for predicting tropism of non-B subtype viruses showed good agreement with the phenotype, but the CRF01-AE subtype was not included (6,23). Moreover, we have shown that these genotypic tools are not valid for predicting the tropism of subtype D viruses (8).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in the envelope gene influence the genotypic prediction of HIV-1 tropism that relies on data on the correlation between genotype and phenotype obtained in countries where subtype B viruses predominate. But the performance of genotypic algorithms can differ from one HIV-1 subtype to another and must be validated for each particular subtype (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Los análisis filogenéticos de secuencias pertenecientes al cluster de subsubtipo F1 que se ha expandido recientemente en Galicia, Thomson et al (2012) varios países europeos estrechamente relacionados con el cluster F de Galicia, que ramifican en posición basal al mismo y la mayoría recolectados varios años antes de la expansión del cluster gallego, Thomson et al (2012) indica que dicho cluster procede de una variante que se expandió previamente por varios países de Europa occidental. Por otra parte, el hecho de que los 7 virus relacionados con el cluster F de Galicia de los que hay datos epidemiológicos todos proceden de varones infectados por vía sexual y 6 son HSH (los dos de Valladolid, dos de Suiza y los dos de Bélgica) sugiere que la variante europea a partir de la cual se originó el cluster de Galicia también se transmite por contacto homosexual.…”
Section: Discussionunclassified
“…8,9 Of the variable domains, the V3 loop has the strongest known link with HIV-1 tropism, and, therefore, V3 is frequently the focus of studies that aim at defining tropism states. Computational approaches have been developed to classify viruses as R5 or X4 tropic based on a small number of genotypic features of the envelope V3 domain, including charge, number of glycosylation motifs and domain length, [10][11][12][13][14] or the ''11/25 rule'' that associates positively charged amino acids at two positions (11 and 25) in the V3 loop. 15 These methods are highly useful in classifying HIV-1 subtypes B and C as either R5 or X4 tropic so that the appropriate therapy can be prescribed.…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Primarily Infecmentioning
confidence: 99%